The generation of compartmentalized nanoparticles containing siRNA and cisplatin using a multi-needle electrohydrodynamic strategy. Issue 18 (25th April 2017) - Pina, Maria F.; Lau, Wai; Scherer, Kathrin; Parhizkar, Maryam; Edirisinghe, Mohan; Craig, Duncan
Abstract : New drug delivery system of compartmentalized three-layered nanoparticles containing an inner core of PLGA-cisplatin, a middle layer of chitosan-siRNA and an outer protective layer of PLGA. Abstract : This study outlines a novel manufacturing technique for the generation of compartmentalized trilayered nanoparticles loaded with an anti-cancer agent and siRNA as a platform for the combination treatment of cancers. More specifically, we describe the use of a multi-needle electrohydrodynamic approach to produce nanoparticles with high size specificity and scalable output, while allowing suitable environments for each therapeutic agent. The inner polylactic-glycolic-acid (PLGA) layer was loaded with cisplatin while the middle chitosan layer was loaded with siRNA. The corresponding polymeric solutions were characterized for their viscosity, surface tension and conductivity, while particle size was determined using dynamic light scattering. The internal structure was studied using transmission electron microscopy (TEM) and Structured Illumination Microscopy (SIM). The inclusion of cisplatin was studied using electron dispersive spectroscopy (EDS). We were able to generate nanoparticles of approximate size 130 nm with three distinct layers containing an outer protective PLGA layer, a middle layer of siRNA and an inner layer of cisplatin. These particles have the potential not only for uptake into tumors via the enhanced permeability and retention (EPR) effect but also the sequential release of the siRNA and chemotherapeutic agent, thereby providing a means of overcoming challenges of targeting and tumor drug resistance.